2012
DOI: 10.1007/s11418-012-0709-0
|View full text |Cite
|
Sign up to set email alerts
|

Dieckol, isolated from Ecklonia stolonifera, induces apoptosis in human hepatocellular carcinoma Hep3B cells

Abstract: Phlorotannins have been reported to demonstrate several biological properties, including antioxidant activity, and activities useful in the treatment of diabetic complications and in chemoprevention of several vascular diseases. In this study, we focused on the apoptosis induced by dieckol, a marine algal phlorotannin isolated from Ecklonia stolonifera, on human hepatocellular carcinoma (HCC) Hep3B cells. Dieckol reduced the numbers of viable cells and increased the numbers of apoptotic cells in a dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…In addition, it also performs a crucial role in the induction of cell death initiated by a variety of stimuli 64. The proteolytic degradation of PARP that takes place at the beginning of apoptosis is caused by the activated caspase-3 65. As demonstrated by the immunoblot analysis, AM treatment significantly increased thee cleaved PARP protein.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it also performs a crucial role in the induction of cell death initiated by a variety of stimuli 64. The proteolytic degradation of PARP that takes place at the beginning of apoptosis is caused by the activated caspase-3 65. As demonstrated by the immunoblot analysis, AM treatment significantly increased thee cleaved PARP protein.…”
Section: Discussionmentioning
confidence: 97%
“…has shown cytocompatible effects to human fetal lung fibroblasts cell line (MRC-5) [28] and macrophage-like form cell (THP-1 cell) [15]. A recent report using dieckol, an isolated compound from Ecklonia stolonifera Okamura algae extracts, also presented more selective effects to Hek-293 compared to a tumor cell line Hep3B [29].…”
Section: Discussionmentioning
confidence: 99%
“…Dieckol is known to be a major phlorotannin of both Seapolynoland Ecklonia cava itself . Various biological studies of dieckol to date have been reported . Lee et al.…”
Section: Introductionmentioning
confidence: 99%